The Effect of Administrative Implementation Principles towards the Effectiveness of Government Services - Halik Halik; Suhendrayatna Suhendrayatna; Irma Yurni; Halimah Halimah (Budapest International Research and Critics University, 2020)
The purpose of this study is to find out the implementation of the principles of public administration, and see the obstacles experienced by the Camat and sub-district staff in implementing the principles of public administration. This study reviews the policy of implementing administrative principles on the effectiveness of government services. Using descriptive-quantitative methods, the sample are 32 employees of the Tiro sub-district office. the results showed that the policy of implementing administrative principles on the effectiveness of the service of the sub-district government had run effectively and good coordination in the field of duties and functions of each employee.